2017
DOI: 10.1007/s00439-016-1756-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of AHSG with alopecia and mental retardation (APMR) syndrome

Abstract: Alopecia with mental retardation syndrome (APMR) is a very rare autosomal recessive condition that is associated with total or partial absence of hair from the scalp and other parts of the body as well as variable intellectual disability. Here we present whole-exome sequencing results of a large consanguineous family segregating APMR syndrome with seven affected family members. Our study revealed a novel predicted pathogenic, homozygous missense mutation in the AHSG (OMIM 138680) gene (AHSG: NM_001622:exon7:c.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Exome capture, library preparation, and sequencing, as well as data analysis, were performed as previously described ( Reza Sailani et al 2017 ). Briefly, exome capture and library preparation were performed using the Agilent SureSelectXT HumanAllExon V5 (product no.…”
Section: Methodsmentioning
confidence: 99%
“…Exome capture, library preparation, and sequencing, as well as data analysis, were performed as previously described ( Reza Sailani et al 2017 ). Briefly, exome capture and library preparation were performed using the Agilent SureSelectXT HumanAllExon V5 (product no.…”
Section: Methodsmentioning
confidence: 99%
“…Only a few families have been identified and affected individuals are characterized by the absence of scalp hair, the absence of eyebrows and eyelashes, and variable intellectual disability. 13 In 1992, a subdivision into three groups of APMR syndrome was proposed depending on the association with microcephaly and epilepsy: 14,15 (1) APMR with microcephaly without epilepsy, (2) APMR without microcephaly, and (3) APMR with microcephaly and epilepsy. To date, variants in the gene coding for the ɑ-2-HS-glycoprotein (AHSG) have been reported in one consanguineous family, suggesting AHSG as a potential cause of APMR.…”
Section: Introductionmentioning
confidence: 99%
“…To date, variants in the gene coding for the ɑ-2-HS-glycoprotein (AHSG) have been reported in one consanguineous family, suggesting AHSG as a potential cause of APMR. 13 Moreover, three loci have been associated with APMR by linkage analyses: APMR1 (MIM 203650), APMR2 (MIM 610422), and APMR3 (MIM 613930) have been mapped to chromosomes 3q26.33-q27.3 (ref. 16 ), 3q26.2-q26.31 (ref.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of ID and alopecia has been reported before [11], but inherited as an autosomal recessive disorder [12]. Both Reza Sailani et al [13] and Besnard et al [14] have recently reported a rare neuroectodermal syndrome with total or partial absence of hair and variable ID. Most of the patients in those studies presented with congenital alopecia, in contrast, individuals from family 2 of our study developed alopecia later in their teens.…”
Section: Discussionmentioning
confidence: 98%